Horizontal transmission of Streptococcus mutans in children attending kindergarten - Retno Indrawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Transmission of Streptococcus mutans (S. mutans), the main pathogen found in dental caries, is particularly prevalent during the first two years of infancy. Numerous children are reportedly infected with S. mutans by their mothers with early initial acquisition of the condition considered to carry a higher risk of subsequent dental caries. Purpose: This research aimed to examine the possibility of horizontal transmission of S. mutans in children attending Surabaya-based kindergartens. Methods: The number of subjects who satisfied the inclusion criteria totaled 146. Dental plaque was collected for one minute with a sterile toothbrush. After completion of an isolation process, 25 S. mutans colonies were identified in Tripticase Cysteine Yeast (TYC) media by means of morphological, microscopic and biochemical tests using API 20 Strept (bioMerieux France). A polymerase chain reaction with OPA-2 and 13 was subsequently used to determine the genotype of S. mutans. Primary data collection was completed by the administering of a questionnaire intended to elicit information regarding the gender, age, diet and medical history of subjects. Results: An arbitrarily primed polymerase chain reaction (AP-PCR) fingerprint profile of the strains isolated from the subjects indicated similarities in five genotypes of S. mutans and differences in 18 genotypes. Conclusion: The study indicated that certain children are similarly infected by S mutans bacteria which might be due to horizontal transmission between classmates.